Aggregate distributional cost-effectiveness analysis: a novel tool for health economic evaluation to inform resource allocation - Shan Jiang; Boyang Li; Bonny Parkinson; Shunping Li; Yuanyuan Gu (Global Health Research and Policy)
Abstract Health equity is a growing concern for policymakers across the globe. Conventional cost-effectiveness analysis (CEA), commonly used in evaluating health interventions, primarily focuses on the average and aggregate health outcomes in the targeted population, neglecting the distributional impacts on health equity. This gap calls for approaches that can quantify the impact of intervention of interest on health equity to support decision-making. Distributional Cost-Effectiveness Analysis (DCEA) offers a framework to assess the distributional impacts of health interventions. Based on DCEA, aggregate DCEA (A-DCEA) was proposed as a practical and simplified alternative to DCEA. Unlike full DCEA, which requires detailed subgroup data, A-DCEA utilizes aggregated data, making it accessible and feasible for broader use. In this commentary, we discuss the rationale for A-DCEA, outline the steps for its implementation, and highlight its applicability. The purpose of this article is to introduce A-DCEA as a pragmatic and accessible tool for evaluating the equity implications of healthcare interventions. A-DCEA can inform policymakers by incorporating equity considerations into healthcare decision-making, particularly when conducting a full DCEA is impractical due to data limitation. A-DCEA provides a valuable and accessible method for evaluating the distributional impact of interventions, promoting health equity in decision-making. Its adoption can lead to more informed health policy that considers health inequities as well as the efficient use of resources.